2018
DOI: 10.1016/j.jot.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Fufang Xian Ling Gu Bao prevents corticosteroid-induced osteonecrosis of the femoral head—A first multicentre, randomised, double-blind, placebo-controlled clinical trial

Abstract: Background/ObjectiveThis is a multicentre, randomised, double-blind, placebo-controlled clinical trial to investigate the safety and efficacy of Chinese herbal Fufang Xian Ling Gu Bao (XLGB) with antiadipogenic compounds for the prevention of corticosteroid (CS)-induced osteonecrosis of femoral head (ONFH).MethodsPatients of both genders, aged between 18 and 65 years, with diseases such as systemic lupus erythematosus, nephrosis, dermatosis and rheumatoid arthritis indicated for CS treatment and who did not sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
(56 reference statements)
0
32
0
Order By: Relevance
“…SAON is a common orthopaedic disease occurring after pulsed/long term corticosteroids (CS) treatment for infectious diseases (such as severe acute respiratory syndrome, SARS) and rheumatoid diseases (such as rheumatoid arthritis, systemic lupus erythematosus, SLE) [6][7][8]. The occurrence of SAON is highly associated with the dosage and duration usage of CS.…”
Section: Introductionmentioning
confidence: 99%
“…SAON is a common orthopaedic disease occurring after pulsed/long term corticosteroids (CS) treatment for infectious diseases (such as severe acute respiratory syndrome, SARS) and rheumatoid diseases (such as rheumatoid arthritis, systemic lupus erythematosus, SLE) [6][7][8]. The occurrence of SAON is highly associated with the dosage and duration usage of CS.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, few randomised clinical trials concerning ONFH can be followed up for a long term. Published studies mostly reported their results after a follow-up duration of only 2 or 3 years [4,33,40], but the previous study had reported that the interval between diagnosis and collapse could be over 4 years in 46% of cases [41]. In comparison to the natural collapse rate of 49% reported by a systematic review that included the most hips with ONFH [27], our study observed a collapse rate of 26% based on prolonged follow-up data, supporting that HGF helps prevent the natural disease progression of ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…Osteonecrosis of the femoral head (ONFH) in SARS survivors could be attributed to the steroid because high cumulative doses of steroids were closely associated with the occurrence of osteonecrosis [3]. Steroid-associated ONFH can progressively break down the underlying bone of the hip joint and thus induce severe premature osteoarthritis of the hip, which would further cause physical disability in these SARS survivors [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations